Majlis As-Shura and the Plurality Principle: Non-Muslims' Representation in the Majlis As-Shura - Kante Hamed (Media of Law and Sharia, 2023)
As-Shura is the research of the opinions in the community, which is represented by competent persons who will give their views and ideas on a given question, a problem, or even a decision that is very important and is attached to the social, economic, or political life of the people. Therefore, some scholars argued that the elected Shüra must consist of a plurality of political parties, including non-Muslims, who have the authority to formulate the laws of the country. Thus, this research aims to study the main discourses of writers and Muslim researchers on the possibility of this plurality in the Majlis as-Shura in an Islamic state and if that could be going against the morale of a tradition of the law of God that we desperately want to implement and apply. Therefore, the study aims to discourse what competencies the Majlis Al-Shura must have. The research was analyzed using the content analysis method related to documents on Islamic law. The article explored the discussion about Majlis al-Shura from an Islamic perspective by relating The arguments of scholars who support the idea that Majlis al-Shura could have a plurality, which is also one of the values of the democratic system, The article supports the idea that non-Muslims could take part in the shura of the Muslim council, but its authority is restricted and should not be directly linked to the thorough legislation and divine law of the Sharia.